1995
DOI: 10.1364/ol.20.000306
|View full text |Cite
|
Sign up to set email alerts
|

Pulse compression and spatial phase modulation in normally dispersive nonlinear Kerr media

Abstract: Numerical simulations show that, because of the spatiotemporal coupling implied by the multidimensional nonlinear Schrödinger equation, self-focusing of ultrashort optical pulses can lead to pulse compression even in the normal-dispersion regime of a nonlinear Kerr medium. We show how this coupling can be further exploited to control the compression by use of spatial phase modulation. Both the compression factor and the position at which the minimum pulse width is realized change with the amplitude of the phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The dispersive terms are defined as follows: β (0) j := β (0) (ω j ) = ω j /c is the wavenumber, β (1) j := ∂β/∂ω| ω=ωj = 1/v gj is the reverse group velocity, and β (2) j := ∂ 2 β/∂ω 2 | ω=ωj is the group velocity dispersion. The parameters z DF j := β (0) j n 0 (ω j )w 2 i , z DSj := t 2 j /β (2) j , z N Lj := w j n 0 /(2n 2 |U 0j | 2 ), w j , t j denote, respectively, the Fresnel diffraction length, the dispersive length, the nonlinear length, the initial spatial width and the initial temporal width of the j-s pulse. In the above notation j = 1, 2, where the subscript j = 1 (j = 2) refers to the anomalous (normal) pulse.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersive terms are defined as follows: β (0) j := β (0) (ω j ) = ω j /c is the wavenumber, β (1) j := ∂β/∂ω| ω=ωj = 1/v gj is the reverse group velocity, and β (2) j := ∂ 2 β/∂ω 2 | ω=ωj is the group velocity dispersion. The parameters z DF j := β (0) j n 0 (ω j )w 2 i , z DSj := t 2 j /β (2) j , z N Lj := w j n 0 /(2n 2 |U 0j | 2 ), w j , t j denote, respectively, the Fresnel diffraction length, the dispersive length, the nonlinear length, the initial spatial width and the initial temporal width of the j-s pulse. In the above notation j = 1, 2, where the subscript j = 1 (j = 2) refers to the anomalous (normal) pulse.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The notation in equations (1) and (2a,b) is as follows [2]: ζ = z/z DF 1 is the longitudinal coordinate normalized to the Fresnel diffraction length of the anomalous pulse, ξ = x/w 1 is the spatial transverse coordinate normalized to the initial spatial width of the anomalous pulse, τ = (t − β (1) 1 z)/t 1 is the local time normalized to the initial temporal width of the anomalous pulse. The parameters σ j = z DF 1 /z DSj , µ = z DF 1 /z DF 2 , r = λ 1 /λ 2 = ω 2 /ω 1 denote, respectively, the dispersion-to-diffraction ratio, the ratio of the Fresnel diffraction length of the anomalous pulse to the Fresnel diffraction length of the normal pulse and, finally, the ratio of the carrier frequency of the anomalous pulse to the carrier frequency of the normal pulse.…”
Section: Appendix Amentioning
confidence: 99%
“…As a result, the pulse envelope shows a profile with a steep leading edge [21], and corresponds to a additional redshifted spectral broadening at higher input energy. At further high input intensity, the sharp pulse peak decays before it outputs the glass, whereas the back of the pulse refocuses [14]. Two-peak pulse is thus formed.…”
Section: Self-compression In Solids Of Un-chirped Laser Pulsesmentioning
confidence: 99%
“…Early in the study of the nonlinear propagation of the femtosecond laser pulses in transparent media, it was found that the self-focusing effect of the intense femtosecond pulses could lead to pulse compression spatially and temporarily in normal-dispersion regime [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This chirp can be spatial, as in the case of a lens in the beam path and/or it can be temporal, as in the case ofthe light beam produced by a semiconductor laser. Several groups have studied the effects of the interaction of nonlinearity, GVD and diffraction for an incident chirped Gaussian pulse [18][19]. It was found that the critical power for self-focusing changes quadratically with the chirp parameter.…”
Section: Gigabit/sec Propagationmentioning
confidence: 99%